Theoretical Diagnostics of Second and Third-order Hyperpolarizabilities of Several Acid Derivatives - Karakas, Asli; Ceylan, Yusuf; Karakaya, Mustafa; Taser, Mehmet; Terlemez, B.B.; Eren, Nuretdin; El Kouari, Youssef; Lougdali, Meriem; Arof, Abdul Kariem; Sahraoui, Bouchtra (De Gruyter, 2019)
The density functional theory (DFT) at B3LYP/ 6-31G(d) level has been utilized to achieve the electric dipole moment (μ), static dipole polarizability (α) and first hyperpolarizability (β) values for ferulic acid (1) and chenodeoxycholic acid (2). The time-dependent Hartree-Fock (TDHF) technique as a powerful quantum chemical method has been implemented to reveal the dynamic α, β and third-order hyperpolarizabilities (γ) of the examined compounds. Our computational conclusions have been compared with the results of similar materials in the literature. The first and second frontier molecular orbitals (MOs) and their band gaps have also been investigated by means of DFT. © 2019 A. Karakas et al., published by De Gruyter.